1993
DOI: 10.1103/physrevlett.70.4138
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb blockade of two-electron tunneling

Abstract: We study the Coulomb blockade in a superconducting grain, connected to two normal electrodes by tunnel junctions. At small bias, the conductance of this system is due to electrons passing in pairs through the grain. The linear conductance is periodic in the gate voltage. The period and the conductance activation energy are determined by the charge 2e, rather than e. At resonance the current first grows linearly with the applied bias and then drops as the quasiparticle transport channel opens up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
137
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(144 citation statements)
references
References 7 publications
7
137
0
Order By: Relevance
“…In this case, the system is at the degeneracy point, since the energies of two ground states with an even number of carriers are the same. The current is then finite for any bias [296], and there is no Coulomb blockade behavior: Cooper pair tunneling starts from zero voltage.…”
Section: A Coulomb Blockadementioning
confidence: 99%
“…In this case, the system is at the degeneracy point, since the energies of two ground states with an even number of carriers are the same. The current is then finite for any bias [296], and there is no Coulomb blockade behavior: Cooper pair tunneling starts from zero voltage.…”
Section: A Coulomb Blockadementioning
confidence: 99%
“…The case of a superconducting island connected to two normal electrodes (NSN geometry), was studied recently in Refs. [4,9,10]. Our method to include interference effects can also be applied to this case.…”
mentioning
confidence: 99%
“…We first review shortly the two-electron tunneling through a superconducting-normal interface as it has been discussed by Wilkins [2] and more recently by Hekking et al [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Quasiparticles having a continuous spectrum are inherently present in any superconducting device and set a fundamental constraint on the coherence time. Quasiparticle "poisoning", first investigated in the context of charge-parity effects in mesoscopic superconductors 7,8,9 , manifests itself also in the experiments with charge qubits 11,12,13,14,15 . It was reported that even at low temperatures (∼10-50mK) quasiparticles are present in the CPB.…”
Section: Introductionmentioning
confidence: 99%